DAMPAK KINERJA DARI KEPEMIMPINAN DAN MOTIVASI KARYAWAN - Mukrodi Mukrodi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study, the researcher intends to know about the problems of performance, leadership and employee motivation. This research uses descriptive quantitative research. The number of samples used was 48 employees, and the sample used was the full sample. The tests used for data analysis included authentication, estimation tests, regression, correlation, determination, and proof of presumption. The conclusion means that leadership has a significant impact on employee performance, with the regression equation Y = 17.505 + 0.571X1. The hypothesis test gets an arithmetic table t > t or (5,522 > 2.013). Motivation (X2) has a significant impact on employee performance. (Y) Using the regression equation Y = 17.501 + 0.578X2. Hypothesis investigation shows that t count > t table or (5 906 > 2 013). While leadership and motivation at the same time have a significant positive effect on employee performance.